Implementasi Religiusitas Siswa dalam Penggunaan Media Sosial Instagram dan Tiktok Melalui Pembelajaran Pendidikan Agama Islam di SMK Miftahul Ulum Muncar Banyuwangi - Siti Khumairoh; Mar Syahid; Nur Faiz Habibah (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) learning in shaping students’ religiosity in their use of social media, particularly Instagram and TikTok, at SMK Miftahul Ulum Muncar Banyuwangi. Religiosity in this study is understood as the manifestation of Islamic values reflected in students’ beliefs, religious practices, attitudes, and behaviors, both in everyday life and in the digital space. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation, involving PAI teachers and students as the main informants. The findings indicate that students’ use of social media is still predominantly oriented toward entertainment, following trends, and the pursuit of self-existence, with a relatively high intensity of use. Nevertheless, some students have utilized social media as a source of information and religious content, although not optimally. PAI learning that applies a contextual approach and connects instructional material with students’ digital realities is able to enhance religious awareness, particularly in terms of social media ethics. However, the effectiveness of PAI learning has not been evenly achieved due to the persistence of overly theoretical material delivery, low levels of active student participation, and limited digital literacy and ethical awareness in social media use.This study concludes that PAI learning plays a strategic role in shaping students’ religiosity in the digital era; however, it needs to be optimized through dialogical, applicable, and digital literacy based learning strategies. Thus, social media is expected not only to serve as a means of entertainment but also as a space for the formation of religious character and the continuous internalization of Islamic values.